Hubungan Perawatan Payudara dengan Produksi ASI pada Ibu Nifas - Faradita Wahyuni; Pratiwi Lumbantobing; Yuni Vivi Santri P.; Selly M. Pasaribu (Universitas Faletehan, 2022)
Breast care is urgent during pregnancy until breastfeeding. Many important things need to do to breastfeed; one of them is to provide a breast care performed when pregnancy reaches 28 weeks or after the completion of labor because it relates to breast milk production. This study aimed to determine the relationship of breast care with breast milk production among postpartum mothers. The type of the research was analytical survey with cross-sectional approach, covering independent variables and dependent variables which were collected and measured at the same time. The populations of this study were 30 people and the samples were 30 people. The data were analyzed by using chi-square test. The data analysis obtained the calculation result of ρ value 0.002 (<0.05). The researchers concluded that there was a relationship between breast care and breast milk production among postpartum mothers. The research results could be a guideline for health educators to do a breast care promotion to mothers with low milk supply.